DSC and HPLC Studies of Some Common Antidiabetic and Antihypertensive Drugs (Bangladesh Pharmaceutical Journal, 2015)
Now-a-days, a significant percentage of our population suffers from diabetes, hypertension and various inflammatory conditions. In such cases antihypertensive, antidiabetic and anti inflammatory drugs are prescribed concomitantly. Therefore, there is a possibility to have drug-drug interactions which may cause various complications to the patients or may be beneficial too. So study of drug-drug interaction is very important. To attain this objective, equimolar homogeneous mixture of naproxen, losartan potassium and pioglitazone HCl (mixture-1) and mixture of lercanidipine, captropril, naproxen and glimepiride (mixture-2) were studied by DSC (differential scanning calorimetry) and HPLC. DSC studies revealed that there was no interaction among naproxen, losartan potassium and pioglitazone HCl but same interaction was observed among lercanidipine, captropril, naproxen and glimepiride. The results obtained from DSC were further verified by HPLC. However, further studies are needed to make any conclusive remarks at this point. In future, the drug-drug interactions involving these molecules will be quantitatively evaluated for more precise predictions of in vivo drug-drug interactions. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22326 Bangladesh Pharmaceutical Journal 17(2): 123-127, 2014